SEGMENTAL PHONEME TEACHING FOR LOWER PRIMARY SCHOOL STUDENTS IN INDONESIA: A NEED ANALYSIS STUDY - Karimah, Syahadah Albaqiyatul; Boeriswati, Endry; Suseno, Muchlas (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study investigates the instructional needs and challenges in teaching English segmental phonemes to lower primary school students in Indonesia. Although pronunciation is a foundational aspect of oral communication, it is often overlooked in early English instruction. Indonesian learners struggle with phonemes absent in their L1, such as /θ/, /ʒ/, and /æ/, leading to persistent mispronunciations. Using a descriptive qualitative approach, data were gathered through interviews with five elementary English teachers from Central Java and Jakarta. Thematic coding with ATLAS.ti revealed 11 key categories related to instructional methods, media use, assessment, and teacher expectations. Findings show that teachers employ simple, intuitive strategies—such as drilling, songs, flashcards, and kinesthetic activities—that align with brain-based learning principles. However, instruction is constrained by limited classroom time, lack of pronunciation-focused training, and inadequate multimedia support. Assessment remains informal and unsystematic, primarily based on observation during classroom activities. Teachers emphasized the need for a structured, engaging, and sustainable pronunciation teaching model, integrated curriculum support, and access to multisensory teaching media. The study highlights the importance of early phoneme instruction to prevent fossilization of errors and to support learners’ long-term communicative competence.